Fatores epidemiológicos e triagem neonatal associados à toxoplasmose gestacional e congênita em Gurupi, Tocantins - Silva, Marcos Gontijo da (2014)
INTRODUCTION: Toxoplasmosis is a parasitic disease caused by the protozoan Toxoplasma gondii. This disease becomes important when present in pregnant women because of the imminent risk of congenital transmission and can promote immediate and late sequelae of concepts, among which stand out the neurological and ocular manifestations. Knowledge of the prevalence and risk factors for its spread are of great relevance. OBJECTIVES: To evaluate the prevalence of gestational and congenital toxoplasmosis and risk factors for transmission of toxoplasmosis in pregnant women Gurupi, Tocantins. METHODS: The study population consisted of 487 pregnant women of which were extracted using a standardized form, sociodemographic, dietary and cultural habits. It was also made of peripheral blood collection performed by serological anti-anti IgM and IgG ELISA. PCR and IgG avidity levels in women and their newborn babies where the mother was IgM was performed. Data were analyzed by comparing the seropositivity with risk factors by means of the odds ratio. RESULTS: The prevalence of IgG antibodies was 68.37% and 5.75% for IgM antibodies. The sociodemographic characteristics associated with risk for toxoplasmosis were; education greater than or equal to eight years, family income at or below minimum wage. Regarding eating habits, there was a significant association between seropositivity and the variables: eating meat, cut raw meat and do not wash the knife and board before cutting the vegetables and frequent intake of vegetables. There were seven cases of vertical transmission and a case of abortion. DISCUSSION: The results confirm the studies carried out in Brazil and abroad as the prevalence of toxoplasmosis and as to the factors involved in the transmission, where the variables studied, meat intake, intake of raw vegetables and use the unwashed cutting board and knife after cutting raw meat, are important risk factors for the pregnant woman acquires toxoplasmosis during pregnancy. CONCLUSION: Gurupi proved to be a municipality with high endemicity of this parasite.